Conservation Subdivision: Construction Phase—Low Impact Development (LID) and Stormwater Treatment - Daniel Penniman; Mark Hostetler; Glenn Acomb (EDIS)
Because so much area in subdivisions is covered by impervious surfaces such as roads, buildings, and driveways, stormwater runoff must be accounted for and treated to prevent flooding and to remove contaminates. Often, stormwater runoff impacts surrounding landscapes and water bodies due to nutrient loading. This 7-page fact sheet discusses the importance of using a more distributed stormwater treatment system that treats runoff closer to the source. Often called Low Impact Development (LID), this stormwater management approach is being used to more effectively remove pollutants from runoff. Written by Daniel Penniman, Mark Hostetler, and Glenn Acomb, and published by the UF Department of Wildlife Ecology and Conservation, March 2012.